Komunikacja polityczna w Internecie na szczeblu lokalnym. Rekonesans badawczy - Choroś, Błażej; Skrabacz, Ewa (Polityka i Społeczeństwo, 2021)
The following paper presents the results of original research focused on analyzing online activities of politicians at the local level. The object of analysis were tools of political communication on the Internet – web pages, personal Facebook accounts, Facebook pages and Twitter accounts – used by the councillors and mayors of cities that are capitals of districts in the Opole Voivodeship. Results of the research confirm the following hypotheses: 1) Politicians at the local level use online tools less often then politicians at the national level; 2) online communication tools are used similarly to traditional media – as one-way communication channels; 3) online communication tools are more intensively used by mayors than councillors.